Collaborative information seeking environments benefiting from holistic ergonomics. Issue 3 (21st September 2015) - Meyer, Anika; Fourie, Ina
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the value of utilising a holistic ergonomic approach, covering engineering, cognitive and social perspectives, to cultivate beneficial and productive collaborative information seeking (CIS) systems and environments, specifically with regard to three main CIS pillars (control, communication and awareness). Design/methodology/approach – A qualitative research approach, based on a selective corpus of CIS literature, was utilised to perform a content analysis to note if terms and concepts normally associated with engineering, cognitive and social ergonomics can be used to eliminate terms reflecting issues related to three CIS pillars (control, communication and awareness) that can benefit from a holistic ergonomic approach. Findings – The content analysis revealed that a fairly extensive amount of holistic ergonomic terminology is prominent within the CIS literature, therefore establishing a connection between the two disciplines: CIS and ergonomics. This suggests that CIS system issues could benefit from the insights of a holistic ergonomic approach. Research limitations/implications – Since this is an exploratory study the scope of CIS literature utilised in the content analysis was limited to a selection considered most important by the authors; this should be supplemented by further research. Practical implications – Intended to instigate interest in further exploration of the beneficial and productive implications and practical application of holistic ergonomics in designing CIS systems and environments. Originality/value – This is the first research paper in the Library and Information Science literature that explores the potential of utilising holistic ergonomics to cultivate CIS systems and environments.